Evacuation speed of human beings in road tunnels at different altitudes - Yan, Guanfeng; Wang, Mingnian; Yan, Tao; Qin, Pengcheng (Tunnelling and underground space technology, 2022)
[Display omitted] •Lower ambient pressure in high-altitude areas lowers people’s athletic capacity.•The illumination of the internal tunnel is lower and impairs the athletic capacity.•Demographic characteristics influence people’s walking speed.•A formula considering various factors is presented to predict the walking speed. There is an increasing number of road tunnels constructed in high-altitude areas of China. Generally, a tunnel is long and narrow. Therefore, when a fire breaks out in a tunnel, it is difficult to get rid of the smoke and the heat, which poses a threat to stranded people. The walking speed of people is the critical factor determining the evacuation time, particularly in high-altitude areas where the ambient pressure is low. In this study, a series of field tests were conducted by considering the environmental parameters to explore the effects of altitude on the people’s walking speed, and the considered parameters include the blood oxygen saturation of people, their heart rate and its variability parameters, ratings of perceived exertion, and walking speed. The results show that ambient pressure, which is about 97 kPa at an altitude of 500 m, decreases to approximately 64 kPa at an altitude of around 3850 m. In other words, the ambient pressure decreases with the increase in the altitude, and the difference in illumination between the internal tunnel and open environment is obvious. More specifically, several factors, including gender, age, tunnel environment, and altitude influence the walking speed, and corresponding reduction coefficients are introduced to reflect the influence of the factors on the walking speed. Finally, based on the field data, a reliable formula is proposed to predict the walking speed at different altitudes.